2020
DOI: 10.32473/edis-ae534-2020
|View full text |Cite
|
Sign up to set email alerts
|

Urban Fertilizer Ordinances in the Context of Environmental Horticulture and Water Quality Extension Programs: Frequently Asked Questions

Abstract: Excess nitrogen (N) and phosphorus (P) in water bodies are a leading cause of water quality degradation statewide. More than 50 Florida counties and municipalities now have formal fertilizer ordinances, which in some cases include fertilizer blackouts, or bans on the usage of N and P fertilizers during certain times of the year. This 8-page document provides information on the underlying issues of fertilizer use, with an emphasis on an urban setting, and outlines the current state of the science on urban ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…An article published in 2020 plainly stated that we as a society do not know for sure if fertilizer bans protect water quality (Dukes et al 2020). According to Dukes et al (2020) and a study funded by the Tampa Bay Estuary Program referenced therein, we would need long-term (greater than seven years) studies on the relationships between fertilizer bans and water quality to confidently assess the efficacy of fertilizer bans, but no study of this duration had been conducted.…”
Section: Background and Justificationmentioning
confidence: 99%
“…An article published in 2020 plainly stated that we as a society do not know for sure if fertilizer bans protect water quality (Dukes et al 2020). According to Dukes et al (2020) and a study funded by the Tampa Bay Estuary Program referenced therein, we would need long-term (greater than seven years) studies on the relationships between fertilizer bans and water quality to confidently assess the efficacy of fertilizer bans, but no study of this duration had been conducted.…”
Section: Background and Justificationmentioning
confidence: 99%
“…Some results of excessive eutrophication are visible: thick mats of algae in the water, scum and foam, odor and taste problems, and wildlife death. These changes can make way for invasive aquatic plants, which can take over like pests and interfere with boating, fishing, and swimming (Dukes et al 2020). In surface waters like lakes and rivers, eutrophication is often a consequence of contaminated water runoff.…”
Section: Effects Of Nutrient Pollution Eutrophicationmentioning
confidence: 99%
“…While numerous studies have indicated that nutrient losses via leaching and runoff are minimal from healthy, properly maintained turfgrass and that turfgrass lawns are sinks of nitrogen (N) in urban watersheds [6][7][8], turfgrass fertilizers are increasingly targeted by management practices and policies aimed at reducing anthropogenic nutrient inputs to aquatic ecosystems [9]. For example, in Florida, more than 50 counties and municipalities have enacted fertilizer ordinances that often prohibit any application of N-and phosphorus (P)-bearing fertilizers to urban lawns during Florida's summer rainy season (June to September) each year [10,11]. The premise behind these bans is that summer rains may lead to increased leaching and runoff losses of N and P applied as fertilizer to lawns, in turn leading to increased anthropogenic nutrient loading to nearby waterbodies.…”
Section: Introductionmentioning
confidence: 99%